2019
DOI: 10.3390/su11133497
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Treatment for Sulfate and Lead Removal from Battery Wastewater

Abstract: In this study, we present a low-cost and simple method to treat spent lead–acid battery wastewater using quicklime and slaked lime. The sulfate and lead were successfully removed using the precipitation method. The structure of quicklime, slaked lime, and resultant residues were measured by X-ray diffraction. The obtained results show that the sulfate removal efficiencies were more than 97% for both quicklime and slaked lime and the lead removal efficiencies were 49% for quicklime and 53% for slaked lime in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…However, significant season variability was only observed for Zn (ANOVA, p < 0.0001) and Al content (ANOVA, p = 0.042) ( Figure 2). Consistent with our results, Vu et al [40] reported an average concentration of Pb in battery wastewater of about 3-15 mg/L. Similarly, Ribeiro et al [41], also reported higher concentration values for Fe (344 ± 96 mg/L), Zn (60 ± 17 mg/L) and Pb (22 ± 15 mg/L) and other heavy metals (Cr, Cu and Ni < 2 mg/L) in lead acid battery industry wastewaters.…”
Section: Heavy Metal Composition Of Industrial Wastewaterssupporting
confidence: 94%
See 1 more Smart Citation
“…However, significant season variability was only observed for Zn (ANOVA, p < 0.0001) and Al content (ANOVA, p = 0.042) ( Figure 2). Consistent with our results, Vu et al [40] reported an average concentration of Pb in battery wastewater of about 3-15 mg/L. Similarly, Ribeiro et al [41], also reported higher concentration values for Fe (344 ± 96 mg/L), Zn (60 ± 17 mg/L) and Pb (22 ± 15 mg/L) and other heavy metals (Cr, Cu and Ni < 2 mg/L) in lead acid battery industry wastewaters.…”
Section: Heavy Metal Composition Of Industrial Wastewaterssupporting
confidence: 94%
“…Wastewater from Industry 1 had significantly higher levels of Al, Cu and Pb, followed by Industry 4, 5, 3 and 2, which could be ascribed to the main processes related to these industries. Physicochemical and elemental characterisation of the automotive battery industry effluent indicates that it is complex and strongly acidic in nature containing a variety of heavy metals above the legislated limits for discharge [40,41]. Heavy metal contents of Industry 1 were of the magnitude in the order of Al > Zn > Pb> Cu > Ni > Cr, with all metal content being consistently above legal permissible limits.…”
Section: Heavy Metal Composition Of Industrial Wastewatersmentioning
confidence: 99%
“…As the main component of LAB, the majority of lead (approximately 85%) is consumed in the production process [9], which encourages the recycling of spent LABs. The recycling of lead grid and plastics have already been commercialized [10][11][12], while the recycling of lead paste and electrolyte are still under intense investigation [13][14][15][16][17]. Spent electrolyte from LABs contains high concentrations of sulfate acid and a certain amount of heavy metals, which are highly corrosive and poisonous and could cause serious environmental crises without proper disposal methods.…”
Section: Introductionmentioning
confidence: 99%
“…The adverse effect caused by lead exposure continues during the life course [22] and affects several key organ systems, e.g., the cardiovascular [23], renal [24,25], and hepatic [26,27] systems. Depending on the concentration of sulfate ions, wastewater is disposed of by precipitation with lime or slaked lime [16,28], crystallization [29] for solutions with high sulfate concentration and exchange resin [30], and sulfate-reducing bacteria (SRB) [31][32][33][34][35] for solutions with low sulfate concentration. Compared with other techniques, SRB methods have the advantages of high removal ratio, low capital, and operation cost and are capable of large scale operation at low sulfate concentrations and medium pH range.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation